y"+2y'+y=2e^-t I tried to find the solution for this nonhomogenous diff. Equation but i could not. First i took a function Y(t)=Ae^-t but i was getting 0=2e^-t. To get rid of that i took another y'+y=2e^-t and found the solution y=2te^-t + ce^-t. Noticed that first part of this finding is solution of my nonhomogenous diff equation so i took another function Y(t)=Ate^-t but then again i am finding the same answer, i need some tips on how to continue. The general solution for this equation as homogenous equation has repeated roots.